THE ADMINISTRATORS’ INFORMATIONAL LEADERSHIP MODEL FOR UNIVERSITIES IN DALIAN CITY - Jing, Yang; Muangman, Pornthep; Tipanark, Peerapong (วารสารวิจัยธรรมศึกษา, 2025)
The objectives of this research were: (1) To study the components and indicators of administrators’ informational leadership. (2) To develop administrators’ informational leadership model for universities in Dalian. The population consists of 13,910 administrators and teachers within 12 undergraduate public universities in Dalian. A stratified random sampling method was used for sampling, totaling 392 person which calculated from G*Power program. The instrument for collecting data was a questionnaire. Descriptive statistics and inferential statistics were used to perform data analysis by using statistical computer software. The findings revealed that 1) administrators’ informational leadership in universities in Dalian consisted of four components: (1) informational technology literacy, (2) informational planning capability, (3) informational management capability, and (4) informational assessment capability. These components were supported by 14 indicators. The developed informational leadership model demonstrated a good fit with the empirical data, with Relative Chi-square (χ2/df) = 1.98, Degree of Freedom (df) = 43, Goodness of Fit Index (GFI) = 0.968, Tucker-Lewis Index (TLI) = 0.988, and Root Mean Square Error of Approximation (RMSEA) = 0.05, meeting the specified criteria. 2) The key components of the model had weights ranging from 0.726 to 1, indicating their significant contribution to informational leadership.